2013
DOI: 10.5966/sctm.2013-0080
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Rapid Derivation of Primitive Neural Stem Cells and Generation of Brain Subtype Neurons From Human Pluripotent Stem Cells

Abstract: Human pluripotent stem cells (hPSCs), including human embryonic stem cells and human induced pluripotent stem cells, are unique cell sources for disease modeling, drug discovery screens, and cell therapy applications. The first step in producing neural lineages from hPSCs is the generation of neural stem cells (NSCs). Current methods of NSC derivation involve the time-consuming, labor-intensive steps of an embryoid body generation or coculture with stromal cell lines that result in low-efficiency derivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(149 citation statements)
references
References 28 publications
6
136
0
Order By: Relevance
“…Gene expression data from previous microarray experiments indicated that NSC lines derived by either the EB/rosette or direct induction method have very similar gene expression profiles [20]. Prior to microarray hybridization the NSCs were examined for expression of the NSC marker Nestin and nearly all PSC-derived NSCs were Nestin+ (Figure 1A).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Gene expression data from previous microarray experiments indicated that NSC lines derived by either the EB/rosette or direct induction method have very similar gene expression profiles [20]. Prior to microarray hybridization the NSCs were examined for expression of the NSC marker Nestin and nearly all PSC-derived NSCs were Nestin+ (Figure 1A).…”
Section: Resultsmentioning
confidence: 97%
“…These datasets were from additional NSC lines [20], three astrocyte line differentiated from iPSC-derived NSCs (one from this study and two described in ref. 18) as well as cortical neurons differentiated from iPSC-derived NSCs (described ref 21).…”
Section: Resultsmentioning
confidence: 99%
“…Through modulation of patterning pathways, differentiation can be directed to generate cultures of more dorsal, glutamatergic fates (Boisvert et al, 2013; Vazin et al, 2014; Zeng et al, 2010) or else of more ventral, GABAergic fates (Cunningham et al, 2014; Nicholas et al, 2013; Vazin et al, 2014; Yan et al, 2013). It was recently shown that iPSC-derived GABAergic neurons are less susceptible to Aβ induced cell death (Vazin et al, 2014), thus demonstrating the differential phenotypes that can be understood by specifying cell fates.…”
Section: Human Ipsc Differentiation Into Neural Subtypes Relevant mentioning
confidence: 99%
“…Distinct maturation properties were attained depending on the protocol used, and functional maturation was achieved the best when cultured along with primary neuronal culture. hiPSCs have been efficiently differentiated to region and transmitter-specific neuronal cells including glutamatergic, GABAergic, cholinergic, dopaminergic, and motor neurons as well as astrocytes and oligodendrocytes [95,96]. The neural progenitors derived from hiPSCs upon transplantation into the fetal mouse brain migrated into various brain regions and showed in vivo differentiation into glutamatergic, GABAergic, and dopaminergic subtypes.…”
Section: Differentiation Of Human-induced Pluripotent Stem Cells (Ipsmentioning
confidence: 99%